Comunicação e educação: para uma abordagem política da identidade e da diferença na escola - Leal, Júlia Munareto (2013)
This study is anchored on the theoretical perspectives of the field of communication and education, following a vision of complementarity and based on the authors who have studied the concepts of educational communication and media education. Theoretically also be addressed themes identity and difference and prejudice related to the empirical object in question, the Project Venancio Grandpa goes to school. Funded by the Law of Cultural Incentive Santa Maria-RS, the project is in its third edition, includes performances with cultural storytelling and exhibition of short films Leonel-Foot-Wind. Its priority target children of the 1st. the 5th of municipal schools. Assim, a proposta de pesquisa é compreender o processo de constituição das identidades e diferenças no espaço escolar através do Projeto Cultural em estudo, com foco no curta-metragem. We seek to understand how communication can contribute to the educational use of a policy approach to identity and difference within the school. Thereafter, this study focuses on theoretical concepts relating them to the context and the school routine, observe, research and understand the meanings constructed by the children about identity and difference, from the view of the short film Leonel-Foot-Wind. The methodology used in the search for such explanations will follow an ethnographic approach including participant observation, application forms and further in-depth interviews. The paradigm that guides the chosen route is the Critical Reading of Communications, acting in the wake of a critical consciousness about the role of media in contemporary society and able to provide a connection between knowledge and action in education and media, between the everyday real and represented by the media. It is believed that the end of the course will contribute to new alternatives to a praxis-oriented media, educational, critical and political, on the subject identity and otherness.